Hierarchy: enhancing performances beyond limits - Sanchez, Clément (National Science Review, 2020)
Living organisms, for their survival and reproduction, have evolved to produce complex hierarchical three-dimensional structures ranging from nanometers to meters with extraordinary and unusual sets of properties. Over the last 20 years, hierarchically porous materials that replicate complex living structures have attracted intense attention from both the academic and industrial worlds. A large variety of domains from biotechnology, biomedicine, catalysis, photocatalysis, optics, sensing, energy conversion and storage, and separation processes to cell therapy have a fervent interest in hierarchically porous materials [1-8].